In silico Analysis of Human Endothelial Cell-specific Molecule 1 and Interleukin-6 Genetic Variants Involved in Coronary Artery Disease - Vineet Kulkarni; Sukanya Shetty; Roopa Bhandary; Yanglem Mary (Biomedical and Biotechnology Research Journal)
Background: Recent epidemiological studies have highlighted the connection between endothelial cell-specific molecule (ESM-1) and interleukin-6 (IL-6) with coronary artery disease. This study aims to assess the influence of nonsynonymous single-nucleotide polymorphisms (nsSNPs) in ESM-1 and IL-6 on protein expression through computational methods. Methods: A total of 141 SNPs in the ESM-1 gene and 22 SNPs in the IL-6 gene were retrieved from the dbSNP database. The pathogenicity of the SNPs was evaluated using SIFT and PolyPhen-2. The functional impact of the SNPs was analyzed using Functional Analysis through Hidden Markov Models, Combined Annotation Dependent Depletion, Protein Analysis through Evolutionary Relationships, PredictSNP, Multivariate Analysis of Protein Polymorphism, Screening for Nonacceptable Polymorphisms, Predictor of human Deleterious Single-nucleotide Polymorphisms, and SNP functional annotation. The MUpro and I-Mutant web tools were used to predict protein stability, and the Group-based Prediction System (GPS)-MSP tool was used for posttranslational modification analysis. SOPMA was utilized to determine the proteins’ secondary structure. Results: SIFT analysis identified 57 intolerant and 65 tolerant SNPs in ESM-1. CADD results indicated that several ESM-1 SNPs were pathogenic, while the majority were nonpathogenic. For IL-6, a small number of SNPs were identified as pathogenic, with the majority being nonpathogenic. The MUpro tool suggested that some ESM-1 SNPs enhanced stability, while the majority decreased protein stability. For IL-6, only a few SNPs increased protein stability, while the majority decreased it. Conclusion: In silico analysis of both ESM-1 and IL-6 SNPs suggests an impact on protein regulation. Further in vitro studies are necessary to validate these findings and their potential role in the pathogenesis of coronary artery disease.